Józefa Jodkowskiego kłopoty z objęciem posady w Wilnie w świetle listów do Wandalina Szukiewicza - Blombergowa, Maria Magdalena (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The National Library in Warsaw contains a collection of manuscript’s documents and other materials of Wandalin Szukiewicz (1852-1919). archaeologist and explorer of Lithuania. They include letters to and from his contemporaries, lovers of antiquity as well as Polish and Russian archaeologists. Of the vast correspondence, the letters of Józef Jodkowski (1890-1950), in which he writes about an offer to take up the post of keeper in the museum of Vilnius, have been used in this paper. His candidature was supported by the Moscow Archaeological Society and personally by its chairwoman Countess P.S. Uvarova as well as by the Archaeological Commission of Petersbourg and the Minister of Education, L.A. Kasso. The Russian administration of Vilnius was bent on Russification of Lithuania and opposed the employment of the Poles and Catholics. For this reason Jodkowski, despite his qualifications, was regarded as an unsuitable candidate. Admittedly, nobody in Vilnius dared to oppose the influential people who supported Jodkowski but he was offered such conditions that he had to resign. The letters used here show how many unknown facts relating to the history of archaeology can still be found in libraries and archives.